Prevalence of Tuberculosis Infection Among Adults of Thiruvananthapuram District of Kerala as Measured by Interferon Gamma Release Assay - A Cross-Sectional Study - Mohan, Aparna; Indu, P.S.; Nair, Sanjeev; Rakesh, P.S.; Saradadevi, K.L.; Rajahamsan, Jyothi (Indian journal of community medicine, 2022)
Background: To achieve the goals of the end tuberculosis (TB) strategy, strategies for management of TB infection (TBI) have to be expanded. The first step to devise policies is to understand the distribution and determinants of TBI in the community. The objectives of the study were to estimate the prevalence of TBI using Interferon Gamma Release Assay (IGRA) and its determinants among the adult population of Thiruvananthapuram district, Kerala. Materials and Methods: A community-based, cross-sectional study using the stratified cluster sampling was carried out among the adults. TBI was detected using IGRA conducted on whole blood sample. Data on determinants were collected using a structured questionnaire by the face-to-face interview. The prevalence of TBI was estimated. Univariate and multivariate analysis was conducted to identify the determinants. Results: Age standardized prevalence of TBI among 396 adults was 20.5% (95% confidence interval [CI] 16.52-24.48). On adjusting for the possible confounders, increasing age (adjusted odds ratio [OR] 1.028; 95% CI 1.008-1.048; P = 0.005), history of contact with active TB disease (adjusted OR 7.61; 95% CI 4.43-13.05; P < 0.001), childhood contact (adjusted OR 8.20; 95% CI 3.14-21.41; P < 0.001), and household contact (adjusted OR 10.12; 95% CI 5.39-18.98; P < 0.001) were found to be the determinants of TBI in this population. Conclusion: The present study observed that nearly one-fifth of the adult population in the Thiruvananthapuram district has TBI. For the programmatic management, factors such as increasing age and contact history may be considered for the elimination of TBI in the state.